Answer:
Subtraction Property of Equality
Step-by-step explanation:
Given
![-x + 1 = -4](https://tex.z-dn.net/?f=-x%20%2B%201%20%3D%20-4)
![-x = -5](https://tex.z-dn.net/?f=-x%20%3D%20-5)
Required
State which property is used
The word that describes the operation is; subtraction property of equality.
This property states that:
if
then
![x - a = y - a](https://tex.z-dn.net/?f=x%20-%20a%20%3D%20y%20-%20a)
So, for the given equation:
![-x + 1 = -4](https://tex.z-dn.net/?f=-x%20%2B%201%20%3D%20-4)
When the subtraction property of equality is applied
![-x + 1 - 1 = -4 - 1](https://tex.z-dn.net/?f=-x%20%2B%201%20-%201%20%3D%20-4%20-%201)
![-x = -5](https://tex.z-dn.net/?f=-x%20%20%3D%20-5)
So:
<em>(a) Subtraction Property of Equality </em>is correct